An infant with congenital heart defects and proteinuria: a case report - Dandan Liu; Yafeng Wang (BMC, 2022)
Abstract Background Branchio-Oto-Renal (BOR) Syndrome is a rare autosomal disorder with a wide variety of clinical manifestations and a high degree of heterogeneity. Typical clinical manifestations of BOR syndrome include deafness, preauricular fistula, abnormal gill slits, and renal malformations. However, atypical phenotypes such as congenital hip dysplasia, congenital heart anomaly or facial nerve paresis are rare in BOR syndrome, and this might be easily misdiagnosed with other congenital disorders. Case presentation We report a 5-month-old boy of BOR syndrome with "congenital heart defects and proteinuria" as clinical features. Initially, as this case mainly presented with symptoms of recurrent respiratory infections and was found to be with congenital heart disease and proteinuria at the local hospital, but he only was diagnosed with congenital heart disease combined with pulmonary infection and anti-infective and supportive treatment was given. Subsequently, during the physical examination at our hospital, left side preauricular pit and branchial fistulae on the right neck were found. Subsequent evaluation of auditory brainstem response and distortion product otoacoustic emission were revealed sensorineural hearing impairment. Results of renal ultrasonography showed small kidneys. Genetic analysis revealed a microdeletion at chromosome 8q13.2-q13.3 encompassing EYA1 gene, this patient was finally diagnosed with BOR syndrome. Then, this patient received transcatheter patent ductus arteriosus closure and hearing aid treatment. Proteinuria, renal function and hearing ability are monitoring by nephrologist and otologist. The patient is currently being followed up until 3 months after discharge and his condition is stable. Conclusion Careful physical examination, detailed history and the implementation of diagnostic laboratory tests can reduce the incidence of misdiagnosis. Genetic sequencing analysis of patients is a key guide to the differential diagnosis of BOR syndrome.